Odpowiedzi

Najlepsza Odpowiedź!
2010-01-15T16:35:15+01:00
2x⁵-5x⁴-3x³=0
x³(2x²-5x-3)=0
x₁³=0→x₁=0


2x²-5x-3=0
Δ=b²-4ac
Δ=25+24
Δ=49
√Δ=7

x₂=(-b-√Δ):2a=(5-7):4=-½

x₃=(-b+√Δ):2a=(5+7):4=3


x₁,x₂ i x₃ to pierwiastki równania
2010-01-15T16:36:30+01:00
Inny zapis tego równania:
x³(2x²-5x-3)=0
x₁ = 0 - pierwiastek potrójny
2x²-5x-3 = 0
Δ = 25-4×2×(-3) = 25+24=49
√Δ = 7
x₂ = 5-7 /4 = -2/2 = -1/2
x₃= 5+7 / 4 = 12/4 = 3

Rozwiązaniem są:
x₁ = 0 - pierwiastek potrójny
x₂ = -1/2
x₃ = 3
2010-01-15T16:39:00+01:00
2x⁵ - 5x⁴ - 3x³ = 0
x³(2x² - 5x - 3 ) = 0 <=> x³ = 0 lub 2x² - 5x - 3 = 0 <=>
x = 0 lub 2*(x -0,5)*(x -3) = 0, bo
Δ = 25 - 4*2*(-3) = 25+24 = 49
√Δ = 7
x2 = [5 -7]/4 = -0,5
x3 = [5+7]/4 = 12/4 = 3
Odp. x1 = 0, x2 = - 0,5 , x3 = 3